Molecular mechanisms and therapeutic advances of peritubular capillary neogenesis in acute kidney injury - Ding, Yuming; Gao, Linmei; Chen, Yi; Qiao, Yanheng; Yang, Bo (Frontiers in Molecular Biosciences, 2025)
Acute kidney injury is a clinical syndrome characterized by a rapid decline in renal function, driven by pathological mechanisms such as renal tubular epithelial cell injury, inflammatory responses, and microcirculatory dysfunction. In recent years, the role of angiogenesis in AKI recovery and regeneration has gained increasing attention. Angiogenesis plays a dual role in tissue repair and pathological remodeling, exhibiting complex spatiotemporal dynamics during AKI progression. This review synthesizes recent advances in understanding the role of angiogenesis in AKI, with the aim of identifying potential diagnostic and therapeutic strategies. Studies indicate that the ischemic-hypoxic microenvironment following AKI activates key signaling pathways, including hypoxia-inducible factor-1α, which subsequently upregulates vascular endothelial growth factor and angiopoietins, thereby modulating intrarenal angiogenesis. Controlled angiogenesis may enhance regional perfusion, mitigate hypoxic injury, and facilitate tubular repair, whereas excessive or dysregulated angiogenesis can contribute to maladaptive vascular remodeling and fibrotic progression. Current research efforts focus on therapeutic strategies aimed at modulating angiogenesis, such as exogenous VEGF administration, endothelial progenitor cell transplantation, and Notch signaling modulation, to promote functional vascular regeneration. However, the precise role of angiogenesis varies across different AKI phases (acute vs recovery), and its interactions with inflammatory and fibrotic pathways remain incompletely understood. Further elucidation of these mechanisms is essential for developing targeted therapeutic interventions.